Correlation between Adsorption and Photocatalysis in the Aqueous System Cr(VI)-TiO2 - Meichtry, Jorge Martin (2025)
The photocatalytic removal of Cr(VI) (0.80 mM, pH 2) using various commercially available photocatalysts (P25, UV100, PC50) was revisited, with particular attention given to Cr(VI) adsorption (as a Cr(VI)-TiO2 surface complex) and the formation of a Cr(III) hydroxide layer during the photocatalytic reduction. Cr(VI) adsorption followed a quasi-Langmuir-type isotherm, and the spectra of the Cr(VI)-TiO2 surface complex were deconvoluted into two Gaussian peaks, red-shifted when a rutile phase was present. Cr(VI) photoreduction exhibited nearly pseudo first-order kinetics, with P25 showing the highest reaction rate. Adsorbed Cr(VI) was reduced by eCB−, and the formed Cr(III) was retained over the TiO2 surface under non-equilibrium conditions, acting as a new adsorption site for Cr(VI). At longer reaction times, partial dissolution of the Cr(III) layer was observed. These findings suggest that the photoreduction kinetics are primarily governed by the slow adsorption of Cr(VI) onto the Cr(III) deposition layer. As an important conclusion, three consecutive processes never mentioned before take place: (1) reduction of adsorbed Cr(VI), (2) formation of Cr(III) over the photocatalyst and (3) adsorption of Cr(VI) over the deposited Cr(III) layer, together with partial Cr(III) redissolution. This insight provides a deeper understanding of the underlying photocatalytic mechanism.